Frequency of Rifampicin Resistance in Primary Pulmonary Tuberculosis at Sheikh Zayed Hospital Rahim Yar Khan - Abdul Salam, Jagdesh Kumar, Muhammad Hanif Chachar, Akhtar Ali, Faheem Ahmed Solangi, Shafi Muhammad, Abdul Waheed, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A World Health organization estimated show that almost 10 million people effect from TB and almost 1.5 million people died from this disease in 2018. Pakistan is ranked 5th in overall TB burden and ranked 4th in drug resistance development of developing countries. About 510,000 case of TB arise every year in Pakistan and 15000 patients develop drug resistance each year. Drug resistance cause huge mortality rate. It should confirm by using drug susceptibility test before treating the patient for drug resistance and for cure. Objective: To find out the frequency of rifampicin resistance in primary pulmonary tuberculosis patient by using drug susceptibility test. Methodology: This cross sectional study was conducted among all patient who visited department of pulmonology of Sheikh Zayed Hospital Rahim Yar Khan from 2016-2018. A total of 1184 smear positive TB patients having no history of ATT intake patient who visited pulmonology department were included in study. Patients sputum was further sent for PCR based Gene Xpert assay for detection of Mycobacterium tuberculosis and rifampicin resistance. Results: A total 1184 TB patients were included in study carried out from 2016 to 2018 at pulmonology Department Sheikh Zayed hospital Rahim Yar Khan. Based on residential locality, 771 (65.11%) belonged to Rahim Yar Khan, 123 (10.38%) to Khanpur, 208 (17.56%) Sadiqabad, 82 (6.92%) Liaqatpur.Out of these 1184 TB cases Rifampicin resistance was detected in 65 (5.5%) cases. In current study rifampicin resistancewas detected in males and females40 (61.5%) and 25 (38.5%) respectively . Conclusion: This study shows that rifampicin resistance among patient is directly affected with socioeconomic status of patient. TB is curable but when a TB patient is resistance to one or multiple drugs especially rifampicin, chance of cure will be less and patient will acquire more resistance to other drugs.